Penggunaan Puzzle Pythagoras sebagai Media Pembelajaran bagi Siswa SMPN Tublopo - Hijriani, Lailin; Handayani, Rika; Lestari Siahaan, Meiva Marthaulina; Wua Laja, Yosepha Patricia; Naimnule, Maria; Seso Delvion, Eduardus Beo (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Every concept in mathematics is related to one another. In addition, a concept can be a prerequisite for another concept. One concept in mathematics is the Pythagorean Theorem. In line with the results of interviews with mathematics teachers at SMPN Tublopo where there are still many students who do not understand the Pythagorean Theorem material and many students are still not focused and do not pay attention to the teacher during the learning process. So a solution is needed to solve the problems being experienced, one of which can be done is to do community service by implementing the Pythagorean puzzle media. Community service activities really help students understand the Pythagorean theorem material with the help of Pythagorean puzzle teaching aids. Based on the results of the pre-test and post-test, it can be seen that there was an increase of 270.83%. And based on the questionnaire, it can be seen that students find it easier to answer math questions, are happier and more enthusiastic when learning uses puzzle media. Students also find it easier to solve problems related to the Pythagorean theorem because of the help of puzzle media. Overall, we can see that there was a positive response from students after this community service was carried out based on the results of the questionnaire given after the activity ended.